2012
DOI: 10.1242/jeb.074401
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of transepithelial ammonia excretion and luminal alkalinization in the gut of an intestinal air-breathing fish, Misgurnus anguilliacaudatus

Abstract: -1). Carbonic anhydrase does not appear to be associated with gut alkalinization under these conditions as ethoxzolamide was without effect on J base . Membrane fluidity of the posterior intestine was low, suggesting low permeability, which was also reflected in a lower mucosal-serosal J amm in the presence of an imposed gradient, in contrast to that in the anterior intestine. To conclude, although the posterior intestine is highly modified for gas exchange, it is the anterior intestine that is the likely site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Ammonium ions (substituting for H + ) then pass into the epithelial boundary layer via an apical Na + /H + exchanger. Here the alkaline nature of the boundary layer facilitates the formation of gaseous ammonia (NH 3 ) which then volatilises (Wilson et al, 2013). The ability of galaxiid fish to volatilise ammonia from the cutaneous surface requires further investigation.…”
Section: Aquatic Normoxia (6 H)mentioning
confidence: 99%
“…Ammonium ions (substituting for H + ) then pass into the epithelial boundary layer via an apical Na + /H + exchanger. Here the alkaline nature of the boundary layer facilitates the formation of gaseous ammonia (NH 3 ) which then volatilises (Wilson et al, 2013). The ability of galaxiid fish to volatilise ammonia from the cutaneous surface requires further investigation.…”
Section: Aquatic Normoxia (6 H)mentioning
confidence: 99%
“…Ionocytes secrete and absorb ions in SW and FW environments, respectively (Hiroi & McCormick ). Although several ionocyte models have been described in different species and environments (Wilson, Laurent, Tufts, Benos, Donowitz, Vogl & Randall ; Wilson, Randall, Donowitz, Vogl & Ip ; Hwang, Lee & Lin ; Wilson, Moreira‐Silva, Delgado, Ebanks, Vijayan, Coimbra & Grosell ), the Na + /K + ‐ATPase (NKA) is the main driving force for ion uptake/secretion in these cells (Hirose et al . ; Hwang et al .…”
Section: Main Osmoregulatory Organs In Flatfish and Teleost In Generalmentioning
confidence: 99%
“…Various studies have shown that ammonia transport occurs often via tissues also responsible for gas exchange and/or osmoregulation such as skin (14,51,63), intestine (49,68,72), nephridial systems (29,32), gills (66,75), kidneys (59), and anal papillae (18,64). Early work on ammonia excretion suggested that transport of NH 3 was purely passive because of its assumed permeability in lipid bilayers (28) and the lack of identification of an NH 3 -transporting protein.…”
mentioning
confidence: 99%